A Late Cretaceous felsic magmatic suite from the Tengchong Block, western Yunnan: integrated geochemical and isotopic investigation and implications for Sn mineralization. (24th August 2020) - Sun, Zhuanrong; Dong, Guochen; Santosh, M; Mo, Xuanxue; Dong, Pengsheng; Wang, Weiqing; Fu, Bin
Abstract: The Tengchong Block within the Sanjiang Tethys belt in the southeastern part of the Tibetan plateau experienced a widespread intrusion of a felsic magmatic suite of granites in its central domain during Late Cretaceous times. Here, we investigate the Guyong and Xiaolonghe plutons from this suite in terms of their petrological, geochemical, and Sr–Nd, zircon U–Pb and Lu–Hf–O isotopic features to gain insights into the evolution of the Neo-Tethys. The Guyong pluton (76 Ma) is composed of metaluminous monzogranites, and the Xiaolonghe pluton (76 Ma) is composed of metaluminous to peraluminous medium- and fine-grained syenogranite. A systematic decrease in Eu, Ba, Sr, P and Ti concentrations; a decrease in Zr/Hf and LREE/HREE ratios; and an increase in the Rb/Ba and Ta/Nb ratios from the Guyong to Xiaolonghe plutons suggest fractional crystallization of biotite, plagioclase, K-feldspar, apatite, ilmenite and titanite. They also show the characteristics of I-type granites. The negative zircon εHf( t ) isotopic values (−10.04 to −5.22) and high δ 18 O values (6.69 to 8.58 ‰) and the negative whole-rock εNd( t ) isotopic values (−9.7 to −10.1) and high initial 87 Sr/ 86 Sr ratios (0.7098–0.7099) of the Guyong monzogranite suggest that these rocks were generated by partial melting of the Precambrian basement without mantle input. The zircon εHf( t ) isotopic values (−10.63 to −3.04) and δ 18 O values (6.54 to 8.69 ‰) of the Xiaolonghe syenogranite are similar to the features of the Guyong monzogranite, and this similarity suggests a cogenetic nature and magma derivation from the lower crust that is composed of both metasedimentary and meta-igneous rocks. The Xiaolonghe fine-grained syenogranite shows an obvious rare earth element tetrad effect and lower Nb/Ta ratios, which indicate its productive nature with respect to ore formation. In fact, we discuss that the Sn mineralization in the region was possible due to Sn being scavenged from these rocks by exsolved hydrothermal fluids. We correlate the Late Cretaceous magmatism in the central Tengchong Block with the northward subduction of the Neo-Tethys beneath the Burma–Tengchong Block.